Changes in the perception of error announcements from the German two-tier enforcement - Marc Berninger (Schmalenbach Journal of Business Research (SBUR), 2024)
When the German financial reporting enforcement was introduced in 2004, the legislator chose an innovative approach: He combined a~private enforcement institution with a~governmental agency while sanctioning was carried out solely by publicly announcing identified accounting errors. Subsequently, investors were confronted with up to then unprecedented 'error announcements' from the enforcement system. For a~sample of 213 announcements from 2006 to 2019, the paper analyzes the adaptation process of investors to this new information. While significant negative market reactions around the announcement dates can be found for the whole observation period, the results also show that the investors' views of the error announcements change over time. Especially in the early years, the observed market reactions are strongly linked to the impact of the accounting error on the firm's financial situation. This link weakens over time and factors related to the nature of the error become more important to investors. In particular, errors that are attributable to the unjustifiable application of professional judgment lead to significantly more negative effects.
Keywords: G18; G41; M41; M42; M48; 650; Accounting errors; Adaptation; Corporate governance; Enforcement; Event study; Exercise of discretion; FREP